GREEN PRODUCTION ANALYSIS FRESH MUSHROOMS PRODUCTS AT PT. ETR - ghofur (Journal Knowledge Industrial Engineering (JKIE), 2022)
Along with Development of the industrial world which is increasingly advanced with the increasing number of industries that have sprung up because of the wide open market share, the greater threat to environmental sustainability is because of industrial companies engaged in the cultivation of champignon mushrooms agriculture, located on the slope of Mount Bromo with an altitude of 1,300 masl . The company started its business in 1999 by cultivating button mushrooms on a trial scale and meeting local market demand. On December 9, 2001, its business expanded from a capacity of 2 units to 6 units to meet national and international market demand (ETR, 2019). The process of implementing green production at PT. ETR in the Cultivation Division can be said to be running because all raw materials and products are environmentally friendly. However, the implementation is implementing green production. Its implementation only refers to energy saving and production cost mapping (GVSM) approach. The purpose of this study was to analyze the green production of fresh mushrooms produced by PT. ETR.